Determinan Minat Berkarir Mahasiswa di Perbankan Syariah - Dama Mustika; Arini, Arini; Dariati, Anis Mahmudah (Akuntansi & Ekonomika, 2024)
This research aims to analyze the factors influencing students' career interests in Islamic banking. With the increasing awareness of Sharia-based financial services and the growth of the Sharia banking industry, it is important to understand the determinants in the career decisions of the younger generation. The research method used was a quantitative survey with 63 respondents distributed among students. The research shows that interest in a career in Islamic banking is greatly influenced by knowledge of Islamic banking, the level of religiosity, job market considerations, and financial rewards. This research suggests the need for improved education regarding Islamic banking and transparency related to careers to attract more interest. These results assist educational institutions and the Islamic banking industry in developing more efficient methods to attract young talent.